Some challenges in identifying academic literacy among master students (Journal of Educational Sciences, 2023)
Academic literacy is the ability to speak in a scientific environment and in discussions with constructive conclusions, be able to discuss, evaluate and compare scientific results, and make a significant contribution to the field of study. Academic literacy development is an urgent issue. The authors discovered a problem with a small number of domestic research on academic literacy. In addition, several issues with improving academic writing abilities among undergraduates are identified. The paper conducted an empirical investigation to measure undergraduates' academic literacy level. The questioning method was used to determine the causes of undergraduates' insufficient academic literacy. The survey included 51 Astana university master students. 52% of students can distinguish academic writing from other writing genres. According to the students, "the younger generation's low interest in studying scientific literature," "the incapacity of students to search: identify, select, and evaluate information," etc. - 3% of respondents, "satisfactory" - 37% — are the causes for the inadequate knowledge of academic writing. Based on the findings of the study, suggestions are made to focus on student motivation and the admission procedure for the magistracy.Keywords: level of academic literacy, master students, challenges, academic writing skills.